An anticlassical political-economic analysis : A vision for the next century - Murakami, Yasusuke (Stanford, Calif Stanford University Press, 1996)
The book offers an alternative framework to classical political economy, analyzing Japan's postwar economic system and presenting a vision for political-economic structures in the coming century.
Keywords: Kinh tế chính trị